Mengangkat Kuliner Indonesia Melalui Bahasa dan Visual di Media Sosial: Perspektif Wacana Pariwisata - Wan Farah Wani Wan Fakhruddin; Muhammad Arfin Muhammad Salim (Politeknik Pariwisata Makassar, 2023)
The growth of culinary tourism has become a tourist attraction in many countries worldwide. Culinary is important in endorsing the uniqueness and authenticity of the country and nation. This paper investigates the role of language and visual images in fostering Indonesian cuisine on social media, Facebook, Instagram, and Twitter in multimodal perspectives. This research adopted multimodal discourse analysis to manipulate the data gained. The study focuses on the language and visual elements employed in social media. The choice of words and stylistic strategies on Facebook, Instagram, and Twitter become the concern of the analysis. The main visual analysis concerns are modality, participant and salience. The find shows that social media relies heavily on exaggerated language and images to foster culinary tourism in Indonesia. It thus contributes to our understanding of how multimodal discourse about Indonesian culinary tourism develops with changing Indonesian tourism.